2006
DOI: 10.1021/om060585r
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Reactions of Bis(η5-cyclopentadienyl)methylzirconium Cations with Ketones and Aldehydes

Abstract: The reactions of the bis(η 5 -cyclopentadienyl)methylzirconium cation (1) with ketones and aldehydes in the gas phase have been studied by Fourier transform ion cyclotron resonance mass spectrometry. Reactions of 1 with a majority of the ketones studied resulted in consecutive addition of one and two substrate molecules and/or elimination of alkanes. Deuterium-labeled substrates and methylzirconocene were used to investigate the mechanistic details. On the basis of DFT calculations, the key products of the eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…C-H bond activation by larger transition metal ion complexes has also been studied recently. [49][50][51][52][53] The Uggerud group investigated the mechanism for C-H bond activation of ethylene by 18e − Rh(III) and 16e − Rh(III) complexes inside the ICR cell in which H 2 elimination was observed in the reaction of ethylene and Cp-Rh(C 2 H 4 -μH) + complexes. 54 DFT calculations showed that vinylic C-H bond activation is an energetically unfavorable process.…”
Section: Introductionmentioning
confidence: 99%
“…C-H bond activation by larger transition metal ion complexes has also been studied recently. [49][50][51][52][53] The Uggerud group investigated the mechanism for C-H bond activation of ethylene by 18e − Rh(III) and 16e − Rh(III) complexes inside the ICR cell in which H 2 elimination was observed in the reaction of ethylene and Cp-Rh(C 2 H 4 -μH) + complexes. 54 DFT calculations showed that vinylic C-H bond activation is an energetically unfavorable process.…”
Section: Introductionmentioning
confidence: 99%
“…Such comparison of gas-phase and condensed phase results and bridging the gap between them has many advantages. Most importantly, gas-phase studies can furnish information which can lead to much better understanding of the role of solvent, ancillary ligand [22,[25][26][27][28][29][30][31][32]. Also, the detection of elusive reaction intermediates may be possible in such gas-phase experiments.…”
Section: Introductionmentioning
confidence: 99%
“…A recent gas-phase study of the reactivity of the bis(g 5 -cyclopentadienyl)methylzirconium cation involved simple ketones and aldehydes [30]. It was found that reactions with a majority of the ketones resulted in consecutive addition of one or two substrate molecules and/or elimination of alkanes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation